Chip varistor and preparation method thereof

By modifying the surface of zinc oxide with single atoms and refining its particle size, a ZnO grain-bismuth-rich grain boundary-np junction effect is formed, which solves the problem of poor nonlinearity of zinc oxide varistors and realizes the preparation of chip varistors with high nonlinear coefficient and stability, which are suitable for industrial production.

CN120965305AActive Publication Date: 2025-11-18东莞可锐电子科技有限公司
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511338642.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-11-18
Estimated Expiration
2045-09-18

AI Technical Summary

Technical Problem

The zinc oxide varistors produced by the existing solid-phase mechanical mixing method have relatively poor nonlinearity, which cannot meet the needs of industrial production.

Method used

By refining the particle size of zinc oxide and group II-VI oxides and performing single-atom surface modification on zinc oxide containing intrinsic defects, chip varistors were prepared. The single-atom modified zinc oxide and nano zinc oxide composites were used to form a ZnO grain-bismuth-rich grain boundary-np junction effect, which improved the nonlinear coefficient and stability.

Benefits of technology

The prepared chip varistors have high nonlinear coefficients, excellent stability and high energy absorption capacity, which reduces production costs and facilitates industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of piezoresistor preparation, in particular to a chip piezoresistor and a preparation method thereof. The chip varistor is prepared by sintering a zinc oxide voltage-sensitive ceramic composition; the zinc oxide voltage-sensitive ceramic composition is composed of a main material and a dopant, wherein the dopant accounts for 2-10 wt% of the total mass of the zinc oxide voltage-sensitive ceramic composition; the main material is a compound formed by nano zinc oxide and monatomic modified zinc oxide or the main material is monatomic modified zinc oxide; the doping agent is formed by matching Bi2O3, Sb2O3 and Cr2O3 with at least one of Co2O3, CoO, MnO2, Mn2O3, NiO, CuO, TiO2, Al2O3, SiO2, Fe2O3 and La2O3, and the doping agent is formed by matching at least one of Bi2O3, Sb2O3, Cr2O3, CoO, MnO2, Mn2O3, NiO, CuO, TiO2, Al2O3, SiO2 The chip piezoresistor prepared by the invention has a high nonlinear coefficient and excellent stability, and solves the problem that the nonlinearity of a zinc oxide piezoresistor produced by an existing solid-phase mechanical mixing method is relatively poor.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of piezoresistor preparation, and particularly relates to a chip piezoresistor and a preparation method thereof. BACKGROUND

[0002] The piezoresistor is a semiconductor ceramic element formed by sintering zinc oxide as a main raw material and other group II-VI oxides (Bi2O3, Sb2O3, Co2O3, CoO, Cr2O3, MnO2, Mn2O3, etc.), which has excellent nonlinear ohmic characteristics, strong transient energy absorption capacity, short response time and other advantages, and is widely used in power systems, electronic circuits, microelectronic circuits and other fields as an overvoltage protector. The zinc oxide piezoceramic has unique voltage-current characteristics, can maintain very small conductivity (equivalent to insulating material) under low voltage, and has very high conductivity and dielectric constant under high voltage, that is, has high nonlinearity in the conductive state and low leakage current under the steady-state working voltage, thereby playing a role in overvoltage protection.

[0003] The zinc oxide in the zinc oxide piezoceramic formula is a non-stoichiometric n-type semiconductor, and the voltage-current characteristics thereof are linear. The intrinsic defects of zinc oxide include oxygen vacancies and zinc interstitial atoms, and these defects cause the zinc oxide to exhibit n-type conductivity. In addition, impurities (such as hydrogen, nitrogen, etc.) in the zinc oxide also have adverse effects on the electrical properties.

[0004] At present, the preparation method of the zinc oxide piezoresistor is mainly the solid-phase mechanical mixing method, which has the advantages of simple preparation process, low preparation cost and other industrial production advantages. The existing solid-phase mechanical mixing method is prepared by ball milling, mixing, molding and sintering of zinc oxide particles and a small amount of group II-VI oxides in a solid state. The uniform distribution of zinc oxide and group II-VI oxides is relatively poor compared with the zinc oxide piezoresistor prepared by chemical co-precipitation method and ultrasonic emulsion co-precipitation method, which directly leads to relatively poor nonlinearity of the prepared zinc oxide piezoresistor. The zinc oxide piezoresistor prepared by the chemical co-precipitation method and the ultrasonic emulsion co-precipitation method cannot meet the requirements of industrial production due to the problems of difficult process control, low yield and high cost. Therefore, the inventors have conducted in-depth research on the uniform distribution of zinc oxide and group II-VI oxides, and provided a chip piezoresistor with high nonlinearity coefficient and a preparation method thereof. SUMMARY

[0005] In order to solve the technical problem of relatively poor nonlinearity of the zinc oxide piezoresistor produced by the existing solid-phase mechanical mixing method, the present application provides a chip piezoresistor and a preparation method thereof. By refining the particle size of zinc oxide and group II-VI oxides and performing single-atom surface modification on the zinc oxide containing intrinsic defects, the prepared chip zinc oxide piezoresistor has high nonlinearity coefficient and excellent stability.

[0006] The sheet type piezoresistor is prepared from a zinc oxide piezoceramic composition. A sheet type piezoresistor is prepared from a zinc oxide piezoceramic composition; the zinc oxide piezoceramic composition is composed of a main material and a dopant, the dopant accounts for 2-10 wt% of the total mass of the zinc oxide piezoceramic composition; the main material is a compound of nano zinc oxide and monatomic modified zinc oxide or the main material is monatomic modified zinc oxide; the dopant is at least one of Bi2O3, Sb2O3, Cr2O3, Co2O3, CoO, MnO2, Mn2O3, NiO, CuO, TiO2, Al2O3, SiO2, Fe2O3 and La2O3.

[0007] The zinc oxide containing intrinsic defects is subjected to monatomic surface modification treatment, which improves the compatible dispersibility of the II-VI group oxides and reduces the intrinsic defects of the zinc oxide after the monatomic surface modification, so as to improve the conductivity, heat conductivity and stability of the zinc oxide, the sheet type piezoresistor prepared from the monatomic modified zinc oxide has high nonlinearity coefficient and excellent stability, and the problem of relatively poor nonlinearity of the zinc oxide piezoresistor prepared by the existing solid phase mechanical mixing method is solved.

[0008] Preferably, the monatomic modified zinc oxide comprises nano zinc oxide and metal monatomic anchored to defect points on the surface of the nano zinc oxide, the nano zinc oxide is n-type zinc oxide with a particle size of ≤500 nm, the metal monatomic is one or a combination of Bi, Sb, Cr, Co, Mn, Ni, Ti, Cu, Al, Fe and La, and the mass ratio of the nano zinc oxide to the metal monatomic is (20-100):1.

[0009] Preferably, the mass ratio of the nano zinc oxide to the metal monatomic is (40-60):1.

[0010] Preferably, the metal monatomic is Bi, Sb, La or the metal monatomic is Bi, Sb, La in combination with at least one of Cr, Co, Mn, Ni, Ti, Cu, Al and Fe.

[0011] Further preferably, the metal monatomic is Bi, Sb, Co, Mn and La, and the mass ratio of Bi, Sb, Co, Mn and La in the metal monatomic is 1:1:1:1:(0.1-1).

[0012] The surface of zinc oxide is modified by Bi, Sb and La as main metal single atoms, Bi, Sb and La are anchored on the defect points of the surface of nano zinc oxide in the form of covalent bond, when the n-p junction effect of the ZnO grain-bismuth-rich grain boundary-ZnO grain formed in the sheet type piezoresistor prepared by using the single atom surface modified zinc oxide is used, the bismuth-rich layer can be more uniformly formed when the single atom surface modified zinc oxide grain is sintered, and the Sb, Co, Mn and La atoms contained on the surface of the bismuth-rich layer, so that the bismuth-rich layer is uniformly doped with relatively more Sb, Co, Mn and La in the sintering process, the height of the grain boundary barrier is improved, and the nonlinear coefficient of the whole is improved.

[0013] Preferably, the preparation method of the single atom modified zinc oxide comprises the following steps: Step one, the nano zinc oxide is placed in a 5-20wt% tartaric acid aqueous solution for ultrasonic dispersion treatment for 1-4h, and then reduced pressure filtration, washing and vacuum drying are carried out to obtain carrier zinc oxide; Step two, the metal single atom precursor is prepared: the water-soluble metal salt is added to high-purity water, and then magnetic stirring is carried out for 0.5-2h, and then ultrasonic dispersion treatment is carried out for 0.5-1h, so that the water-soluble metal salt is fully dissolved to obtain the metal single atom precursor; Step three, under magnetic stirring, the carrier zinc oxide in step one is added to the metal single atom precursor in step two at a feeding speed of 0.05-0.5g / min, and the mass ratio of the carrier zinc oxide to the metal single atom in the metal single atom precursor is (20-100) : 1, after the feeding of the carrier zinc oxide is completed, magnetic stirring is continued for 4-24h, and then ultrasonic dispersion treatment is carried out for 1-4h, and then rotary evaporation is carried out at 80-100 DEG C to remove water, and then vacuum drying is carried out to obtain a solid material; Step four, the solid material is subjected to wet planetary ball milling to obtain superfine powder, and then the obtained superfine powder is calcined at 400-600 DEG C for 4-12h, and then planetary ball milling is carried out to obtain the required single atom modified zinc oxide.

[0014] Preferably, the water-soluble metal salt is any one or a combination of multiple of chlorides, nitrates, sulfates, acetates and acetylacetone salts.

[0015] The preparation method of the single atom modified zinc oxide in the application is relatively simple and mature, and the production cost of the single atom modified zinc oxide can be reduced, and the performance advantage of the sheet type piezoresistor can be improved.

[0016] Preferably, the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1-2% Bi2O3, 1-2.5% Sb2O3, 0.5-1% Cr2O3, 0.6-1.2% Co2O3, 0.6-1.2% Mn2O3, 0.5-1% NiO, 0.01-0.10% La2O3, and the balance being monatomic modified zinc oxide.

[0017] By optimizing the selection of dopants in the zinc oxide varistor ceramic composition, the chip varistor is endowed with higher nonlinearity coefficient and energy absorption capacity, lower leakage current, and improved overall piezoelectric performance and high safety and reliability.

[0018] The application provides a preparation method of a chip varistor. The preparation method of the chip varistor comprises the following steps: Step one, preparation of monatomic modified zinc oxide; Step two, accurately metered main materials and dopants are uniformly mixed to obtain a mixture, the obtained mixture is placed in a planetary ball mill for wet ball milling, the solid-liquid ratio is 1:10-40, a dispersing agent is pure water or an ethanol aqueous solution, wet ball milling is performed for 2-8 h under nitrogen protection, and then filtration, washing, and vacuum drying are performed to obtain a zinc oxide varistor ceramic composition; Step three, 100 parts by weight of the zinc oxide varistor ceramic composition is mixed with 6-8 parts by weight of a binder, and then granulation treatment is performed on the mixture in a disc granulator, and the granulated product is sieved through a 50-120 mesh screen to obtain varistor ceramic granules; Step four, the varistor ceramic granules in step three are put into a mold for dry pressing to obtain a sheet-shaped pressing sample, the obtained sheet-shaped pressing sample is subjected to sintering treatment in a muffle furnace, and then the sheet-shaped pressing sample is cooled to room temperature to obtain a chip varistor.

[0019] Preferably, in step four, the varistor ceramic granules in step three are put into a mold, and a sheet-shaped pressing sample is formed by dry pressing at a pressure of 200±20 MPa and a pressure maintaining time of 60-120 s, the obtained sheet-shaped pressing sample is subjected to sintering treatment in a muffle furnace, and the sintering treatment program is as follows: the temperature is raised to 550-650 ℃ at a rate of 200-300 ℃ / h, the sample is subjected to glue removal treatment for 30-45 min, then the temperature is raised to 850-900 ℃ at a rate of 400-600 ℃ / h, the temperature is raised to 1150-1250 ℃ at a rate of 1000-1200 ℃ / h, and the sample is kept at the temperature for 2-4 h, the temperature is lowered to 850-900 ℃ at a rate of 100-200 ℃ / h, the sample is kept at the temperature for 0.5-1 h, the temperature is lowered to 400-450 ℃ at a rate of 200-400 ℃ / h, and the sample is naturally cooled to room temperature in the open furnace, thereby obtaining a chip varistor.

[0020] By optimizing the pressing parameters and sintering parameters, the microstructure is uniformly formed in a segmented heating manner, the molten zinc oxide is slowly precipitated from the liquid phase in a segmented cooling manner, the defects in the grain and the grain boundary are reduced, the internal stress is released, the electrical performance of the high disc type varistor is improved, the disc type varistor has higher nonlinear coefficient, higher energy absorption capacity and lower leakage current, and the overall use stability and safety reliability of the disc type varistor are improved.

[0021] In summary, the present application has the following advantages: 1、The disc type varistor in the present application has the advantages of high nonlinear coefficient, high energy absorption capacity, high safety reliability, and low leakage current, and solves the problem of relatively poor nonlinearity of the zinc oxide varistor produced by the existing solid phase mechanical mixing method.

[0022] 2、The preparation method of the present application is synthesized and prepared by the industrialized solid phase mechanical mixing method, the overall preparation method is relatively simple, the process technology is mature, and industrialized production and manufacturing are easy to realize, thereby reducing the production cost of the disc type varistor. DETAILED DESCRIPTION

[0023] In order to further understand the creativity and technical progress of the present application, the preferred embodiments of the present application are discussed in detail below in combination with examples and comparative examples.

[0024] Example: A disc type varistor is made of a zinc oxide pressure-sensitive ceramic composition prepared by a solid phase mechanical mixing method. The zinc oxide pressure-sensitive ceramic composition is composed of 90-98wt% of main materials and 2-10wt% of dopants.

[0025] The dopant is at least one of Bi2O3, Sb2O3, Cr2O3, Co2O3, CoO, MnO2, Mn2O3, NiO, CuO, TiO2, Al2O3, SiO2, Fe2O3, and La2O5. Specifically, the zinc oxide pressure-sensitive ceramic composition is made of raw materials with the following mass percentages: 1-2% Bi2O3, 1-2.5% Sb2O3, 0.5-1% Cr2O3, 0.6-1.2% Co2O3, 0.6-1.2% Mn2O3, 0.5-1% NiO, 0.01-0.10% La2O3, and the balance of main materials.

[0026] The main material is a complex of nano-zinc oxide and single-atom modified zinc oxide or the main material is single-atom modified zinc oxide.

[0027] The content of nano-zinc oxide in the main material can be adjusted to control the high nonlinear coefficient a of the prepared chip-type varistor, different nonlinear coefficient a values of the chip-type varistor can be prepared according to the requirements of the actual application scene, the market competitiveness of the product is improved, the use amount of single-atom modified zinc oxide is reduced by adding nano-zinc oxide, the total production cost of the product is optimized, the positioning and layout of chip-type varistor products with different nonlinear coefficient a values are facilitated, and commercial profit maximization is sought.

[0028] The single-atom modified zinc oxide includes nano-zinc oxide and metal single atoms anchored to defect points on the surface of the nano-zinc oxide, the nano-zinc oxide is n-type zinc oxide with a particle size of ≤500 nm, the nano-zinc oxide can be directly purchased from the market or prepared by existing synthesis methods such as a precipitation method, a sol-gel method, a direct method or an indirect method in a laboratory. In order to commercialize application, the nano-zinc oxide carrier used in the application is directly purchased from existing nano-zinc oxide products.

[0029] The metal single atoms are one or a combination of Bi, Sb, Cr, Co, Mn, Ni, Ti, Cu, Al, Fe and La. Preferably, the metal single atoms are Bi, Sb and La, or the metal single atoms are Bi, Sb and La in combination with at least one of Cr, Co, Mn, Ni, Ti, Cu, Al and Fe.

[0030] Further preferably, the metal single atoms are Bi, Sb, Co, Mn and La, and the mass ratio of Bi, Sb, Co, Mn and La in the metal single atoms is 1:1:1:1:(0.1-1). The mass ratio of the nano-zinc oxide to the metal single atoms is (20-100):1, preferably the mass ratio of the nano-zinc oxide to the metal single atoms is (40-60):1.

[0031] The preparation method of the single-atom modified zinc oxide includes the following steps: Step one, the nano-zinc oxide is placed in a 5-20wt% tartaric acid aqueous solution for ultrasonic dispersion treatment for 1-4h, and then reduced pressure filtration, washing and vacuum drying are performed to obtain a carrier zinc oxide; Step two, preparation of metal monatomic precursor: water-soluble metal salt is added to high-purity water, the water-soluble metal salt is any one or a combination of multiple of chlorides, nitrates, sulfates, acetates, acetylacetone salts, and is subjected to magnetic stirring for 0.5-2h and ultrasonic dispersion treatment for 0.5-1h, and the water-soluble metal salt is fully dissolved to obtain the metal monatomic precursor; Step three, under magnetic stirring, the carrier zinc oxide in step one is added to the metal monatomic precursor in step two at a feeding speed of 0.05-0.5g / min, the mass ratio of the carrier zinc oxide to the metal monatomic in the metal monatomic precursor is (20-100):1, after the feeding of the carrier zinc oxide is completed, the magnetic stirring is continued for 4-24h, and then ultrasonic dispersion treatment is performed for 1-4h, and the rotary evaporation treatment is performed at 80-100℃ to remove water, and the solid material is obtained after vacuum drying; Step four, the solid material is subjected to wet planetary ball milling to obtain superfine powder, the obtained superfine powder is calcined at 400-600℃ for 4-12h, and the planetary ball milling is performed after natural cooling to room temperature to obtain the required monatomic modified zinc oxide.

[0032] A preparation method of a chip type piezoresistor, comprising the following steps: Step one, preparation of monatomic modified zinc oxide; Step two, accurately metered main materials and dopants are mixed according to a proportion to obtain a mixture, the obtained mixture is placed in a planetary ball mill for wet ball milling, the solid-liquid ratio is 1:10-40, a dispersant is pure water or an ethanol aqueous solution, and the wet ball milling is performed under nitrogen protection for 2-8h, and the zinc oxide piezoceramic composition is obtained after filtration, washing and vacuum drying; Step three, 100 parts by weight of the zinc oxide piezoceramic composition is mixed with 6-8 binders and placed in a disc granulator for granulation treatment, and the piezoceramic granules are obtained after screening through a 50-120 mesh screen; Step four, the piezoceramic granules in step three are put into a mold to form a sheet-shaped compression sample in a dry compression mode at 200±20MPa / pressure maintaining for 60-120s, and the obtained sheet-shaped compression sample is subjected to sintering treatment in a muffle furnace, and the sintering treatment program is as follows: the temperature is raised to 550-650℃ at a rate of 200-300℃ / h, the glue is removed for 30-45min, then the temperature is raised to 850-900℃ at a rate of 400-600℃ / h, the temperature is raised to 1150-1250℃ at a rate of 1000-1200℃ / h, the temperature is maintained for 2-4h, the temperature is lowered to 850-900℃ at a rate of 100-200℃ / h, the temperature is maintained for 0.5-1h, the temperature is lowered to 400-450℃ at a rate of 200-400℃ / h, and the furnace is opened for natural cooling to room temperature, and the sheet type piezoresistor is obtained.

[0033] Preparation example 1: a preparation method of monatomic modified zinc oxide, comprising the following steps: Step one, under magnetic stirring at 200 rpm, 10 parts by weight of near-spherical nano-zinc oxide CW-ZnO-002 (Shanghai Super-Wei Nanometer Technology Co., Ltd.) with an average particle size of 200 nm was added to 200 parts by weight of a 20wt% tartaric acid aqueous solution at a feeding rate of 0.5 g / min. After the addition of nano-zinc oxide was completed, the magnetic stirring was maintained at 200 rpm for 2 hours, followed by ultrasonic dispersion treatment for 1 hour at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W. After the ultrasonic dispersion treatment was completed, the mixture was subjected to reduced pressure filtration, and the wet material obtained by filtration was washed three times with pure water. The wet material was then placed in a vacuum drying oven for vacuum drying at a temperature of 105°C for 2 hours. The carrier zinc oxide was obtained after the vacuum drying was completed. Step two, preparation of metal monatomic precursor: at room temperature, 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, and 2.54 parts by weight of lanthanum chloride heptahydrate were added to 1000 parts by weight of high-purity water. After magnetic stirring at 200 rpm for 2 hours, the mixture was subjected to ultrasonic dispersion treatment for 1 hour at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W. The water-soluble metal salt was fully dissolved to obtain the metal monatomic precursor. Step three, under magnetic stirring, 60 parts by weight of the carrier zinc oxide in step one was added to the metal monatomic precursor in step two at a feeding rate of 0.2 g / min. The ratio of the total mass of bismuth, antimony, and lanthanum in the metal monatomic precursor to the mass of the carrier zinc oxide was 20:1. After the addition of the carrier zinc oxide was completed, the magnetic stirring was maintained at 200 rpm for 20 hours, followed by ultrasonic dispersion treatment for 2 hours at an ultrasonic frequency of 40 kHz and an ultrasonic power of 800 W. The mixture was then subjected to rotary evaporation at 100°C to remove water. The obtained powder was placed in a vacuum drying oven for vacuum drying at a temperature of 105°C for 2 hours to obtain a solid material. Step four, the solid material prepared in step three is put into a planetary ball mill, zirconium oxide is used as grinding beads, and an ethanol aqueous solution (the volume ratio of ethanol to water is 2:1) is used as dispersant, the solid-liquid ratio is 1:25, ball milling is carried out at 80 rpm for 30 min, then reduced pressure filtration is carried out, the wet material obtained by filtration is washed with pure water for three times during the reduced pressure filtration process, the wet material is placed in a vacuum drying oven for vacuum drying treatment, the vacuum drying temperature is 105℃, the vacuum drying time is 2 h, ultrafine powder is obtained, the obtained ultrafine powder is placed in a muffle furnace for calcination treatment, heating to 450℃ at a rate of 10℃ / min, calcination for 4 h, then heating to 600℃ at a rate of 10℃ / min, calcination for 8 h, cooling to 200℃ at a rate of 200℃ / h, and natural cooling to room temperature, the obtained powder is put into a planetary ball mill for ball milling and refinement treatment, zirconium oxide is used as grinding beads, and an ethanol aqueous solution (the volume ratio of ethanol to water is 2:1) is used as dispersant, the solid-liquid ratio is 1:25, ball milling is carried out at 200 rpm for 15 min, at 100 rpm for 30 min, and at 60 rpm for 30 min, then reduced pressure filtration is carried out, the wet material obtained by filtration is washed with pure water for three times during the reduced pressure filtration process, the wet material is placed in a vacuum drying oven for vacuum drying treatment, the vacuum drying temperature is 105℃, the vacuum drying time is 2 h, and the required monatomic Bi / Sb / La modified nano zinc oxide is prepared.

[0034] Preparation example 2 is different from preparation example 1 in that, in step two of the preparation method of the monatomic modified zinc oxide, 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added into 1500 parts by weight of high-purity water, magnetic stirring is carried out at 200 rpm for 2 h, and then 1 h of ultrasonic dispersion treatment is carried out, the ultrasonic frequency is 40 kHz, and the ultrasonic frequency is 800 W, so that the water-soluble metal salt is fully dissolved to obtain a metal monatomic precursor; in step three, 80 parts by weight of the carrier zinc oxide in step one is added into the metal monatomic precursor in step two under magnetic stirring at a feeding rate of 0.2 g / min, the ratio of the carrier zinc oxide to the total mass of the four metal monatomic bismuth, antimony, lanthanum, and cobalt in the metal monatomic precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring is maintained at 200 rpm for 20 h, then 2 h of ultrasonic dispersion treatment is carried out, the ultrasonic frequency is 40 kHz, and the ultrasonic frequency is 800 W, the obtained powder is placed in a vacuum drying oven for vacuum drying treatment, the vacuum drying temperature is 105℃, and the vacuum drying time is 2 h, so that the solid material is obtained, the remaining steps are the same, and monatomic Bi / Sb / La / Co modified nano zinc oxide is prepared.

[0035] Preparation Example 3 is different from Preparation Example 1 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, and 3.61 parts by weight of manganese chloride tetrahydrate are added to 1500 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 80 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the four metal single atoms of bismuth, antimony, lanthanum, and manganese in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring is maintained at 200 rpm for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn modified nano-zinc oxide.

[0036] Preparation Example 4 is different from Preparation Example 1 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, and 3.61 parts by weight of manganese chloride tetrahydrate are added to 1500 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 80 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the four metal single atoms of bismuth, antimony, lanthanum, and manganese in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring is maintained at 200 rpm for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn modified nano-zinc oxide.

[0037] Preparation Example 5 differs from Preparation Example 1 in that in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.05 parts by weight of nickel chloride hexahydrate are added to 2000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 100 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the metal single atoms of bismuth, antimony, lanthanum, manganese, and nickel in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn / Ni modified nano-zinc oxide.

[0038] Preparation Example 6 differs from Preparation Example 1 in that in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 2000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 100 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the metal single atoms of bismuth, antimony, lanthanum, manganese, and nickel in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn / Ni modified nano-zinc oxide.

[0039] Preparation Example 7 differs from Preparation Example 1 in that in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 4.05 parts by weight of nickel chloride hexahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 2000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 100 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the metal single atoms of bismuth, antimony, lanthanum, cobalt, and nickel in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment, the vacuum drying temperature is 105°C, vacuum drying is performed for 2 h, and a solid material is obtained, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Co / Ni modified nano-zinc oxide.

[0040] Preparation Example 8 differs from Preparation Example 1 in that in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, 4.05 parts by weight of nickel chloride hexahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 2500 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 120 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the metal single atoms of bismuth, antimony, lanthanum, manganese, cobalt, and nickel in the metal single-atom precursor is 20:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment, the vacuum drying temperature is 105°C, vacuum drying is performed for 2 h, and a solid material is obtained, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn / Co / Ni modified nano-zinc oxide.

[0041] Preparation Example 9 is different from Preparation Example 6 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 4000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 200 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the five metal single atoms of bismuth, antimony, lanthanum, manganese, and cobalt in the metal single-atom precursor is 40:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing the single-atom Bi / Sb / La / Mn / Co modified nano-zinc oxide.

[0042] Preparation Example 10 is different from Preparation Example 6 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 6000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the water-soluble metal salt is fully dissolved to obtain the metal single-atom precursor; in step three, under magnetic stirring, 300 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the five metal single atoms of bismuth, antimony, lanthanum, manganese, and cobalt in the metal single-atom precursor is 60:1, after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, and then ultrasonic dispersion treatment is performed for 2 h, the ultrasonic frequency is 40 kHz, the ultrasonic power is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment at a vacuum drying temperature of 105°C for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing the single-atom Bi / Sb / La / Mn / Co modified nano-zinc oxide.

[0043] Preparation Example 11 is different from Preparation Example 6 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 8000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the water-soluble metal salt is fully dissolved to obtain a metal single-atom precursor; in step three, under magnetic stirring, 400 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the five metal single atoms of bismuth, antimony, lanthanum, manganese, and cobalt in the metal single-atom precursor is 80:1, and after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, followed by 2 h of ultrasonic dispersion treatment, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment, the vacuum drying temperature is 105°C, and vacuum drying is performed for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn / Co modified nano-zinc oxide.

[0044] Preparation Example 12 is different from Preparation Example 6 in that, in step two of the preparation method of the single-atom modified zinc oxide, the metal single-atom precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 8000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the water-soluble metal salt is fully dissolved to obtain a metal single-atom precursor; in step three, under magnetic stirring, 500 parts by weight of the carrier zinc oxide in step one is added to the metal single-atom precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the five metal single atoms of bismuth, antimony, lanthanum, manganese, and cobalt in the metal single-atom precursor is 100:1, and after the feeding of the carrier zinc oxide is completed, magnetic stirring at 200 rpm is maintained for 20 h, followed by 2 h of ultrasonic dispersion treatment, the ultrasonic frequency is 40 kHz, the ultrasonic frequency is 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment, the vacuum drying temperature is 105°C, and vacuum drying is performed for 2 h to obtain a solid material, and the remaining steps are the same, thereby preparing single-atom Bi / Sb / La / Mn / Co modified nano-zinc oxide.

[0045] Preparation Example 13 is different from Preparation Example 6 in that: in the preparation method of monatomic modified zinc oxide, in step two, the metal monatomic precursor is prepared: 2.32 parts by weight of bismuth nitrate pentahydrate, 3.44 parts by weight of antimony acetylacetone, 2.54 parts by weight of lanthanum chloride heptahydrate, 3.61 parts by weight of manganese chloride tetrahydrate, and 4.04 parts by weight of cobalt chloride hexahydrate are added to 15000 parts by weight of high-purity water, and after magnetic stirring at 200 rpm for 2 h, ultrasonic dispersion treatment is performed for 1 h, ultrasonic frequency 40 kHz, ultrasonic frequency 800 W, and the water-soluble metal salt is fully dissolved to obtain a metal monatomic precursor; in step three, under magnetic stirring, 750 parts by weight of the carrier zinc oxide in step one is added to the metal monatomic precursor in step two at a feeding rate of 0.2 g / min, the ratio of the total mass of the carrier zinc oxide to the metal monatomic bismuth, antimony, lanthanum, manganese, and cobalt in the metal monatomic precursor is 150:1, and after the feeding of the carrier zinc oxide is completed, the magnetic stirring is maintained at 200 rpm for 20 h, followed by 2 h of ultrasonic dispersion treatment, ultrasonic frequency 40 kHz, ultrasonic frequency 800 W, and the obtained powder is placed in a vacuum drying box for vacuum drying treatment, vacuum drying temperature 105°C, vacuum drying for 2 h, to obtain a solid material, and the remaining steps are the same, to prepare monatomic Bi / Sb / La / Mn / Co modified nano-zinc oxide.

[0046] Example 1: A chip varistor is made of a zinc oxide varistor ceramic composition prepared by a solid phase mechanical mixing method. The zinc oxide varistor ceramic composition is composed of 93.7wt% of main materials and 6.3wt% of dopants.

[0047] Specifically, the zinc oxide varistor ceramic composition is made of raw materials in the following mass percentages: 1.5% of Bi2O3, 2% of Sb2O3, 0.5% of Cr2O3, 0.8% of Co2O3, 0.8% of Mn2O3, 0.65% of NiO, 0.05% of La2O3, and 93.7% of the monatomic Bi / Sb / La modified nano-zinc oxide in Preparation Example 1.

[0048] A method for preparing a chip varistor, comprising the following steps: Step one, the preparation of monatomic modified zinc oxide is described in Preparation Example 1; Step two, according to the formula of the zinc oxide varistor ceramic composition, 1.5 parts by weight of Bi2O3, 2 parts by weight of Sb2O3, 0.5 parts by weight of Cr2O3, 0.8 parts by weight of Co2O3, 0.8 parts by weight of Mn2O3, 0.65 parts by weight of NiO, 0.05 parts by weight of La2O3, 93.7 parts by weight of the monatomic Bi / Sb / La modified nano-zinc oxide in Preparation Example 1 are put into a small dispersion kettle, mixed and dispersed at 400 rpm for 4 h under nitrogen protection, fully mixed and uniform to obtain a mixture, the obtained mixture is placed in a planetary ball mill for wet ball milling, zirconium oxide is used as grinding beads, the dispersing agent is an ethanol aqueous solution (the volume ratio of ethanol to water is 2:1), the solid-liquid ratio is 1:25, the ball milling is carried out at 320 rpm for 30 min and at 160 rpm for 240 min, then reduced pressure filtration is carried out, the wet material obtained by filtration is washed with pure water for three times during the reduced pressure filtration process, and the wet material is placed in a vacuum drying box for vacuum drying treatment, the vacuum drying temperature is 105℃, and the vacuum drying time is 2 h, to prepare the zinc oxide varistor ceramic composition; Step three, 100 parts by weight of the zinc oxide varistor ceramic composition is mixed with 6.5 parts by weight of PVA binder, and then placed in a disc granulator for granulation treatment, and sieved through a 60-mesh screen, to obtain the varistor ceramic granules; Step four, the varistor ceramic granules in step three are put into a mold to form a sheet-shaped compression sample by dry pressing at 200 MPa / pressure maintaining for 120 s, and the obtained sheet-shaped compression sample is placed in a muffle furnace for sintering treatment, and the sintering treatment program is as follows: the temperature is raised to 580℃ at a rate of 250℃ / h, the glue is discharged for 45 min, then the temperature is raised to 875℃ at a rate of 500℃ / h, the temperature is raised to 1200℃ at a rate of 1000℃ / h and maintained for 4 h, the temperature is lowered to 875℃ at a rate of 200℃ / h and maintained for 1 h, the temperature is lowered to 400℃ at a rate of 400℃ / h, and the furnace is opened for natural cooling to room temperature, to obtain a sheet-shaped varistor resistor.

[0049] The difference between Example 2 and Example 1 is that the zinc oxide varistor ceramic composition is prepared from the following raw materials in mass percentage: 1.5% of Bi2O3, 2% of Sb2O3, 0.5% of Cr2O3, 0.8% of Co2O3, 0.8% of Mn2O3, 0.65% of NiO, 0.05% of La2O3, and 93.7% of the monatomic Bi / Sb / La / Co modified nano-zinc oxide in Preparation Example 2.

[0050] Example 3 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn modified nano-zinc oxide in Preparation Example 3.

[0051] Example 4 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Ni modified nano-zinc oxide in Preparation Example 4.

[0052] Example 5 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Ni modified nano-zinc oxide in Preparation Example 5.

[0053] Example 6 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 6.

[0054] Example 7 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Co / Ni modified nano-zinc oxide in Preparation Example 7.

[0055] Example 8 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co / Ni modified nano-zinc oxide in Preparation Example 8.

[0056] Example 9 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 9.

[0057] Example 10 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 10.

[0058] Example 11 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 11.

[0059] Example 12 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% of the single atom Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 12.

[0060] Example 13 differs from Example 9 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 20% near-spherical nano-zinc oxide CW-ZnO-002 having an average particle size of 200 nm, 73.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide of Preparation Example 9.

[0061] Example 14 differs from Example 9 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 30% near-spherical nano-zinc oxide CW-ZnO-002 having an average particle size of 200 nm, 63.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide of Preparation Example 9.

[0062] Example 15 differs from Example 9 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 40% near-spherical nano-zinc oxide CW-ZnO-002 having an average particle size of 200 nm, 53.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide of Preparation Example 9.

[0063] Example 16 differs from Example 9 in that the zinc oxide varistor ceramic composition is made from the following mass percentages of raw materials: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 50% near-spherical nano-zinc oxide CW-ZnO-002 having an average particle size of 200 nm, 43.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide of Preparation Example 9.

[0064] Example 17 differs from Example 9 in that the zinc oxide varistor ceramic composition is made from the following raw materials in mass percentage: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 60% near-spherical nano-zinc oxide CW-ZnO-002 with an average particle size of 200 nm, 33.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 9.

[0065] Comparative Example 1 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following raw materials in mass percentage: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% near-spherical nano-zinc oxide CW-ZnO-002 with an average particle size of 200 nm.

[0066] Comparative Example 2 differs from Example 1 in that the zinc oxide varistor ceramic composition is made from the following raw materials in mass percentage: 1.5% Bi2O3, 2% Sb2O3, 0.5% Cr2O3, 0.8% Co2O3, 0.8% Mn2O3, 0.65% NiO, 0.05% La2O3, 93.7% mono-atomic Bi / Sb / La / Mn / Co modified nano-zinc oxide in Preparation Example 13.

[0067] Comparative Example 3 differs from Example 1 in that in Step 4, the varistor ceramic granules in Step 3 are put into a mold to form a sheet-shaped compression sample by dry pressing at 200 MPa / pressure maintaining for 120 s, and the obtained sheet-shaped compression sample is placed in a muffle furnace for sintering treatment, and the sintering treatment procedure is as follows: increasing the temperature to 580 ℃ at a rate of 250 ℃ / h for 45 min for degassing, then increasing the temperature to 875 ℃ at a rate of 500 ℃ / h, increasing the temperature to 1200 ℃ at a rate of 1000 ℃ / h for 4 h, decreasing the temperature to 875 ℃ at a rate of 200 ℃ / h for 1 h, decreasing the temperature to 400 ℃ at a rate of 400 ℃ / h, and opening the furnace for natural cooling to room temperature, to obtain a sheet-shaped varistor resistor.

[0068] The sheet-shaped varistor resistors in Examples 1-17 and Comparative Examples 1-3 are measured for the varistor voltage gradient, leakage current and energy absorption capacity according to the test methods specified in GB / T 16528-1996 “Zinc Oxide Varistor Ceramic Materials for Varistor Resistors”, and the non-linear coefficient is measured according to the test method specified in GB / T 10193-1997.

[0069] Table 1: Test parameter table of sheet-shaped varistor resistors in Examples 1-17 and Comparative Examples 1-3 It can be seen from the combination of Examples 1-8 and Comparative Example 1 and Table 1 that the sheet type voltage-dependent resistor prepared by using the single-atom modified nano zinc oxide as the main material in the application has the advantages of high nonlinearity coefficient, high energy absorption capacity, high safety and reliability, and low leakage current. It can be seen from the combination of Example 6 and Examples 1-5, Examples 7-8 and Table 1 that the single-atom Bi / Sb / La / Mn / Co modified nano zinc oxide synthesized by the metal atoms in a ratio of Bi / Sb / La / Mn / Co = 1:1:1:1:1 has a potential gradient of the sheet type voltage-dependent resistor of 567.5 V·mm -1 , a high nonlinearity coefficient α = 87.71, a high energy absorption capacity EA = 300.5 J / cm 3 , a leakage current density J L = 1.05 uA·cm -2 , and excellent electrical performance.

[0070] It can be seen from the combination of Example 6, Examples 9-12 and Comparative Example 2 and Table 1 that the single-atom Bi / Sb / La / Mn / Co modified nano zinc oxide synthesized by controlling the ratio of the total mass of the metal single atoms of bismuth, antimony, lanthanum, manganese and cobalt in the metal single atom precursor to the carrier zinc oxide to be (20-60):1 has a potential gradient of the sheet type voltage-dependent resistor of ≥540 V·mm -1 , a high nonlinearity coefficient α≥84, a high energy absorption capacity EA≥290 J / cm 3 , a leakage current density J L ≥1.25 uA·cm -2 , and relatively excellent electrical performance. Considering the production cost comprehensively, it is appropriate to control the ratio of the total mass of the metal single atoms of bismuth, antimony, lanthanum, manganese and cobalt in the metal single atom precursor to the carrier zinc oxide to be (40-60):1 during the synthesis of the single-atom Bi / Sb / La / Mn / Co modified nano zinc oxide.

[0071] It can be seen from the combination of Example 1 and Comparative Example 3 and Table 1 that the sheet type voltage-dependent resistor prepared by sintering and forming in the application has relatively better electrical performance. The segmented heating mode makes the microstructure uniform, the segmented cooling mode makes the molten zinc oxide slowly precipitate from the liquid phase, reduces the defects in the grain and at the grain boundary, and also releases internal stress to improve the electrical performance of the high sheet type voltage-dependent resistor, endows the sheet type voltage-dependent resistor with higher nonlinearity coefficient, higher energy absorption capacity and lower leakage current, and improves the overall use stability and safety and reliability of the sheet type voltage-dependent resistor.

[0072] In combination with Embodiment 9 and Embodiments 13-17 and in combination with Table 1, it can be seen that as the content of the near-spherical nano-zinc oxide in the zinc oxide varistor ceramic composition increases, the electrical properties of the chip varistor show a downward trend; when the content of the near-spherical nano-zinc oxide is in the range of 20-40wt%, the downward trend of the electrical properties of the chip varistor is relatively slow; and when the content of the near-spherical nano-zinc oxide is >40wt%, the electrical properties of the chip varistor decrease significantly, and thus, from the perspective of the electrical properties of the chip varistor, the content of the near-spherical nano-zinc oxide in the zinc oxide varistor ceramic composition is preferably controlled to be 20-40wt%. In addition, chip varistors have different requirements for their electrical properties according to different actual application scenarios, and by controlling the content of the nano-zinc oxide, the high nonlinearity coefficient, energy absorption capacity and leakage current density of the prepared chip varistor can be adjusted, and the single-atom modified nano-zinc oxide / nano-zinc oxide-based chip varistor with low cost and excellent electrical properties is prepared, which is beneficial to optimizing the total production cost of the product, improving the market competitiveness of the product, facilitating the positioning and layout of chip varistor products with different nonlinearity coefficient α values, and seeking maximum commercial profit.

[0073] In summary, the chip varistor in the present application has the advantages of high nonlinearity coefficient (α≥68), high energy absorption capacity (EA≥235.0J / cm 3 ), high safety and reliability, low leakage current (J L ≤2.0uA•cm -2 ), and solves the problem of poor nonlinearity of zinc oxide varistors produced by the solid-phase mechanical mixing method. The zinc oxide varistor ceramic composition in the present application is synthesized by the industrialized solid-phase mechanical mixing method, and thus the preparation method of the present application is relatively simple and the process technology is mature, facilitating industrialized production and manufacturing, reducing the production cost of the chip varistor, and improving the market competitiveness of the chip varistor product.

[0074] It should be noted that the specific embodiments are only an explanation and description of the technical solutions of the present application, and are not a limitation of the present application. Those skilled in the art can make non-creative modifications to the embodiments according to their needs after reading the present specification, but as long as the modifications are within the scope of the claims of the present application, they are protected by the Patent Law.

Claims

1. A chip varistor, characterized in that: The chip varistor is sintered from a zinc oxide varistor ceramic composition; the zinc oxide varistor ceramic composition consists of a main material and a dopant, the dopant accounting for 2-10 wt% of the total mass of the zinc oxide varistor ceramic composition; the main material is a compound formed by nano zinc oxide and single-atom modified zinc oxide, or the main material is single-atom modified zinc oxide; the dopant is composed of at least one of Bi2O3, Sb2O3, Cr2O3 combined with Co2O3, CoO, MnO2, Mn2O3, NiO, CuO, TiO2, Al2O3, SiO2, Fe2O3, and La2O3.

2. A chip varistor according to claim 1, characterized in that: The single-atom modified zinc oxide includes nano-zinc oxide and metal single atoms anchored to defect sites on the surface of nano-zinc oxide. The nano-zinc oxide is n-type zinc oxide with a particle size ≤500nm. The metal single atoms are one or more combinations of Bi, Sb, Cr, Co, Mn, Ni, Ti, Cu, Al, Fe, and La. The mass ratio of nano-zinc oxide to metal single atoms is (20-100):

1.

3. A chip varistor according to claim 2, characterized in that: The mass ratio of the nano-zinc oxide to the metal single atom is (40-60):

1.

4. A chip varistor according to claim 3, characterized in that: The metal single atom is Bi, Sb, or La, or the metal single atom is Bi, Sb, or La combined with at least one of Cr, Co, Mn, Ni, Ti, Cu, Al, or Fe.

5. A chip varistor according to claim 4, characterized in that: The metal single atoms are Bi, Sb, Co, Mn, and La, and the mass ratio of Bi, Sb, Co, Mn, and La in the metal single atoms is 1:1:1:1: (0.1~1).

6. A chip varistor according to claim 2, characterized in that: The method for preparing the single-atom modified zinc oxide includes the following steps: Step 1: Place the nano zinc oxide in a 5-20 wt% tartaric acid aqueous solution and ultrasonically disperse for 1-4 hours. Then filter under reduced pressure, wash, and vacuum dry to obtain carrier zinc oxide. Step 2, preparation of metal single-atom precursor: Add water-soluble metal salt to high-purity water, stir magnetically for 0.5-2 hours, and then perform ultrasonic dispersion treatment for 0.5-1 hours to fully dissolve the water-soluble metal salt and obtain the metal single-atom precursor; Step 3: Under magnetic stirring, the carrier zinc oxide from Step 1 is added to the metal single-atom precursor from Step 2 at a feeding rate of 0.05-0.5 g / min. The mass ratio of the carrier zinc oxide to the metal single-atom precursor is (20-100):

1. After the carrier zinc oxide is added, magnetic stirring is continued for 4-24 hours, followed by ultrasonic dispersion treatment for 1-4 hours. The water is removed by rotary evaporation at 80-100℃, and the solid material is obtained after vacuum drying. Step 4: The solid material is wet-milled into ultrafine powder. The obtained ultrafine powder is calcined at 400-600℃ for 4-12 hours and then naturally cooled to room temperature before being refined by planetary ball milling to obtain the desired single-atom modified zinc oxide.

7. A chip varistor according to claim 6, characterized in that: The water-soluble metal salt is any one or a combination of chloride, nitrate, sulfate, acetate, and acetylacetone salts.

8. A chip varistor according to claim 2, characterized in that: The zinc oxide varistor ceramic composition is made from the following raw materials in the indicated mass percentages: 1-2% Bi₂O₃, 1-2.5% Sb₂O₃, 0.5-1% Cr₂O₃, 0.6-1.2% Co₂O₃, 0.6-1.2% Mn₂O₃, 0.5-1% NiO, 0.01-0.10% La₂O₃, with the balance being single-atom modified zinc oxide.

9. A method for preparing a chip varistor according to any one of claims 1-8, characterized in that: The steps are as follows: Step 1: Preparation of single-atom modified zinc oxide; Step 2: Mix the accurately measured main material and dopant evenly according to the formula to obtain a mixture. Place the mixture in a planetary ball mill for wet ball milling with a solid-liquid ratio of 1:10-40. The dispersant is pure water or an aqueous ethanol solution. Wet ball mill for 2-8 hours under nitrogen protection. Filter, wash, and vacuum dry to obtain the zinc oxide varistor ceramic composition. Step 3: Mix 100 parts by weight of zinc oxide pressure-sensitive ceramic composition with 6-8 parts by weight of binder and place the mixture in a disc granulator for granulation. The mixture is then sieved through a 50-120 mesh screen to obtain pressure-sensitive ceramic granules. Step four: The varistor ceramic granules from step three are put into a mold and dry-pressed to obtain a sheet-shaped pressed sample. The obtained sheet-shaped pressed sample is placed in a muffle furnace for sintering treatment, and cooled to room temperature to obtain a sheet varistor.

10. The preparation method according to claim 9, characterized in that: In step four, the varistor ceramic granules from step three are placed into a mold and dry-pressed at 200±20MPa for 60-120s to obtain a sheet-shaped pressed sample. The obtained sheet-shaped pressed sample is then placed in a muffle furnace for sintering. The sintering procedure is as follows: the temperature is increased to 550-650℃ at 200-300℃ / h and the binder is removed for 30-45 minutes. Then, the temperature is increased to 850-900℃ at 400-600℃ / h, increased to 1150-1250℃ at 1000-1200℃ / h and held for 2-4 hours. The temperature is then decreased to 850-900℃ at 100-200℃ / h and held for 0.5-1 hour. Finally, the temperature is decreased to 400-450℃ at 200-400℃ / h and allowed to cool naturally to room temperature after the furnace is opened to obtain the sheet-type varistor.

Citation Information

Patent Citations

  • Low-temperature sintered zinc oxide voltage-sensitive ceramic material and preparation method thereof

    CN102633498A

  • Zinc oxide piezoresistor material with high electric potential gradient

    CN104478428A

  • Low-temperature sintered high-performance high-voltage ZnO varistor material

    CN104860671A

  • Low-temperature sintering zinc oxide varistor material and preparation method thereof

    CN105272205A

  • Series of inorganic antibacterial mildew-proof monatomic catalysts and preparation method thereof

    CN111266099A